Coexistence and characterization of Tet(X5) and NDM-3 in the MDR-Acinetobacter indicus of duck origin. (January 2021) - Tang, Biao; Yang, Hua; Jia, Xu; Feng, Youjun
Abstract: Tigecycline and carbapenem are last-resort antibiotics for serious infections caused by pathogens with multi-drug resistance (MDR). Whereas, bacterial pathogens with co-resistance to tigecycline and carbapenem are poorly addressed. Here we report a tigecycline- and carbapenem-resistant Acinetobacter indicus strain HY20 of duck origin, which co-produces Tet(X5) and NDM-3. Tet(X5) is harbored by a novel plasmid pAI01 (116, 992 bp long), which carries 10 antimicrobial resistance genes (AMRs), and heavy metal resistance system cobalt-zinc-cadmium ( czc ) gene cluster. Unlike that tet (X5) is located in the res - tet (X5)- xerD segment of plasmid, the chromosomal bla NDM-3 is flanked by insertion IS Aba125 . Collectively, our result represents an example of co-carriage of tet (X5) and bla NDM-3, heightening the importance of AMR surveillance needed in poultry production. Highlights: A Tet(X5) and NDM-3-coproducing A. indicus strain HY20 is identified, giving the resistance to tigecycline and carbapenem. Tet(X5) is harbored by a novel plasmid pAI01 (116, 992 bp long), which carries 10 antimicrobial resistance genes (AMRs). The tet (X5) is organized in the res - tet (X5)- xerD segment of plasmid pAI01, whereas bla NDM-3 is located in the chromosome.